Improving Teachers' Competence in Designing Educational Marketing Posters Through Canva Training at Madrasah Aliyah - Nurul Hikmah; Syahmidi; Slamet Riyadi; Abdul Gofur; Dakir (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
This training aims to improve teachers' skills in designing educational marketing posters using the Canva application. The method used is participatory action research. The subjects assisted in this activity were 20 people. The results of the community service show that teachers' skills in designing marketing posters using the Canva application have increased. Before the training, 18 participants lacked basic knowledge of designing marketing posters using the Canva application, while 2 people already possessed this knowledge. After the training, teachers' knowledge and skills increased. 15 people were able to design educational marketing posters, while 5 people were still unable to use the Canva application to create educational marketing posters. The benefits of this training for teachers and madrasas are to make the marketing of the Educational Institutions they manage more efficient and attractive.